Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
2.
a) c + (c-d) = c + c - d = 2c - d
b) 2y - (y + 4) = 2y - y - 4 = y - 4
c) (2x+y) - (x-4y) = 2x+y - x+4y = x + 5y
d) (a+b) - (2a-b) - (a-2b) = a+b -2a + b - a +2b = -2a + 4b
e) 2(x-y) +x -2y = 2x -2y +x -2y = 3x -4y
f) 5b(b-3a) = 5b² - 15ab
e) 2(x-y) +x - 2y = 2x -2y +x -2y = 3x - 4y
g) 5a(a-3b) = 5a² - 15ab
Odpowiedź:
a) c + (c-d) = 2c - d
b) 2y - (y + 4) = 2y - y - 4 = y - 4
c) (2x + y) - (x - 4y) = 2x + y - x + 4y = x + 5y
d) (a + b) - (2a - b) - (a - 2b) = a + b - 2a + b - a + 2b = a - 2a - a + b + b + 2b =
= - 2a + 4b
e) 2( x - y) + x - 2y = 2x - 2y + x - 2y = 3x - 4y
1 f ) 5b(b - 3a) = 5b2 - 15ab
2 f ) 5a(a - 3b) = 5a2 - 15ab
Duże dwójki obok np. 5b2 to jest potęga